Women Who Work According to Khaled Aboue El-Fadl - Poetri Leharia Pakpahan; Muhammad Ikhsannudin; Muhammad Maulana Nur Kholis (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
This article aims to discuss the views of working women according to Khaled Aboue el-Fadl, which will discuss. First, First, who is Khaled Aboue el-Fadl? Second, what is the scope of working women? Third, what are the pertinent examples of cases and solutions from working women? This research uses an analytical study method, namely an examination of library information sources such as books, magazines, documents, notes, historical material. This methodology is used to elucidate an analytical and descriptive analysis of working women according to the corpus of Khaled Aboue el-Fadl. These results indicate that the goal in Islam is a reflection of the function that women who work are actually not really permitted because women actually have to be at the house of the household manager. However, the Islamic view also contains the concept that women who work are also asked to contribute to the family's livelihood, especially for the welfare of the family. Further, it is expected that the woman must wear clothes that cover her eyes so that she can avoid seeing that which is not her muhrim and not to Allah who achieves His pleasure.